Hubungan Praktek Pengaturan Diet Dengan Perilaku Emosional Pada Penyandang Autism Spectrum Disorder (ASD) Usia 3-7 Tahun Di Kota Depok - - Mukhfi; S.A. Nugraheni; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Autism spectrum disorder (ASD) is a pervasive developmental disorder characterized by the development that appears before the age of 3 years , characteristic function abnormalities in three areas, social interaction, communication, limited and repetitive behavior. UNESCO in 2011 , there were 35 million people with ASD in the entire world, 6 of 1000 people in the world have been suspect ASD. While in Indonesia, the ratio of 8 out of every 1000 people. Child asd have allergic to nutrient substance that causes disruption brain functions consequently emotion. This study aims to analyze relationship the practice of diet between with the emotional ASD children aged 3-7 years in Depok. This research uses a cross-sectional study with survey method. The population in this study is child with ASD was therapy in 5 clinic therapy for children with special needs (Anak Mandiri, Talenta Optima, Lentera Insan, Kriebel, Rumah Autis Depok). using the total sampling method 35 children was respondents. using Chi-square for analysis data with 5% significance level. The result showed children with ASD has emotional stable more on child with diet (70,6 %) than child is not on a diet (16 %). The statistics chi-square obtained value p-value 0,001. The concluded that diet practices haved a relationship with emotional in ASD children ages 3-7 years in Depok city